Biodegradable carbonate apatite nanoparticle as a delivery system to promote afatinib delivery for non-small cell lung cancer treatment - Maarof, Nian N. N.; Abdulmalek, Emilia; Fakurazi, Sharida; Abdul Rahman, Mohd Basyaruddin (MDPI, 2022)
Nanomedicine-based drug-delivery systems have significant interest in cancer treatment, such as improving the stabilities and biocompatibilities, precise targeting, and reducing toxicities for non-cancerous cells. Herein, this study presents the synthesis and characterisation of carbonate apatite nanoparticles (nCA) and encapsulated afatinib (AFA) as promising drug delivery candidates for lung cancer treatment. nCA/AFA was synthesised and physicochemically characterised, then the encapsulation capacity, drug loading, and cumulative drug release profile were evaluated. Powder X-ray diffraction (PXRD) confirmed that the synthesised nCA is apatite. Fourier-transform infrared spectroscopy (FTIR) results confirmed the drug loading into the nanoparticles. High-resolution transmission electron microscopy (HR-TEM) determined the morphology of nCA and nCA/AFA and the diameters of 47.36 ± 3.16 and 42.97 ± 2.78 nm, respectively, without an unaltered nCA phase. Encapsulation efficiency (%) and drug loading (%) were 55.08% ± 1.68% and 8.19% ± 0.52%. Brunauer–Emmett–Teller (BET) and dynamic light-scattering (DLS) results revealed that the synthesised nCA is mesoporous, with a surface area of 55.53 m2/g, and is negatively charged. Atomic force microscopy (AFM) showed increasing roughness of nCA/AFA compared to nCA. The drug release from the nano-formulation nCA/AFA demonstrated slow and sustained release compared to the pure drug. Accordingly, nCA/AFA represents a promising drug delivery system for NSCLC treatment.